A review of Vietnamese Scolopocryptops Newport, 1844 (Chilopoda: Scolopendromorpha), with a description of S. hoanglieni n. sp. and the updated generic list of species - Le, Son X.; Schileyko, Arkady A.; Nguyen, Anh D. (Zootaxa, 2023)
The Vietnamese fauna of the genus Scolopocryptops Newport, 1844 was reviewed based on recently collected specimens and material from Zoological Museum of the Moscow Lomonosov State University (ZMMU) and Naturhistorisches Museum Wien (NHMW). As a result of study of 164 specimens from 13 sampling regions, four species have been recognized, of which S. rubiginosus C.L. Koch, 1878 and S. spinicaudus Wood, 1862 already reported from Vietnam, S. hoanglieni described as n. sp., and S. capillipedatus (Takakuwa, 1938) for the first time recorded for this country. S. broelemanni esulcata Attems, 1938 was redescribed and confirmed as a valid. The COI fragments were obtained for the above mentioned species and the K2P genetic divergence between Vietnamese Scolopocryptops species was preliminarily estimated. New data on intraspecific variations of spiracle number in Scolopocryptops, an identification key for East Asian species and the general list of species of Scolopocryptops are provided.